The Effect of Heat Holding Time on the Structure and Tensile Strength of the Product during the Thermo-Mechanical Processing of Dual Phase Steel Production - Trần Công Thức; Tạ Thị Yến; Trần Danh Vũ; Đoàn Văn Đô; Đặng Văn Hữu (Journal of Technical Education Science, 2025)
Advanced high - strength steels (AHSS) is melted from MIREX sponge iron in induction furnace, this AHSS composed only carbon, maganese and silicon elements, but they have higher strength from 600 to 1000 MPa and elongation from 18 to 35 % than those of high - strength, low - alloy steels (HSLA) in same composition due to using special processing. The paper presents the results of mechanical - thermo research to create dual-phase structures (ferrite and martensite) of steel with chemical composition 0,12% C - 1,45% Mn - 0,95% Si - 0,42% Cr - 0,18% Cu, with high purity of impurities 0,022% P, 0,013% S. The martensite phase is composed of islands that account for a proportion from 12% - 25,3%; mechanical properties achieved: tensile strength sb (695 - 823 MPa), yield strength sc (541 - 618 MPa) and total elongation d50 (27,8 - 21,3%). The results have shown that this steel grade can be applied to manufacture parts requiring high strength and good ductility in the production of automobile and and civil production.